Actitudes Ambientales del poblador en el asentamiento humano Versalles en el distrito de Punchana Loreto 2021 - Macedo Rios, Francia Milagros (2022)
This research had the objective of studying environmental attitudes in the inhabitants of the human settlement in 2021. The investigation, by its approach, was a quantitative, forward-looking strategy, with a general descriptive level and nonexperimental research design. The target population was 1556 inhabitants (1556) with at least one year of residence and living in the area. The sample also consisted of 112 inhabitants who were present at the time of the application of the data collection instrument, taking into account inclusion and exclusion criteria. The technique used was the survey. The applied tool was the questionnaire with ten positive and negative statements, which passed the validity (Aiken's validity index) and reliability (Cronbach's alpha test) tests. The data obtained through the data collection instrument was analyzed considering the research objectives and hypothesis and subsequently expressed in a Basic Data Matrix (BDM) and analyzed, processed, and tabulated through SPSS version 25. The results are as follows: 39.3% of the villagers showed a favorable general environmental attitude being the predominant one compared to the unfavorable attitude of 29.4%. Then, 56.3% of the villagers showed a positive cognitive attitude. Also, 56.3% showed a favorable affective attitude towards environmental conservation. 50% of the villagers showed a reactive approach. According to gender, there was a predominance of positive attitude in both with 57.1% and 42.9%. Likewise, according to the educational level of the inhabitants, a predominance of favorable attitudes was found in the illiterate and primary education levels. Whereas in the secondary and higher education levels, unfavorable and very unfavorable attitudes predominated with 53.8% and 100%, respectively.